Socio-economic status and their impact on scholastic performance (achievement) - Mashilwane, Mahlotle Pauline (University of Limpopo, 2001)
The aim of this study was to examine the impact of socio-economic factors on scholastic performance (achievement) ofleamers in the secondary school. The study was conducted in the Southern Region of the Northern Province, in the Nebo District. The Southern Regio which is made up of basically Nebo and Sekhukhune, forms part of the former Lebowa and is basically rural. A literature study was-conducted, which unravelled and brought into surface factors of social and economic nature, which are contrary to effective learning and contributes towards poor performance, especially in public secondary schools. Literature study revealed that learners from disadvantaged backgrounds especially in the rural communities have their learning process heavily affected and disturbed by social and economic factors. An empirical survey was also conducted to establish the views and opinions of parents, educators and the learners themselves. A qualitative research method was used. Letebele Marishane Secondary School in Ngwaritsi circuit was used as a case study. Educators completed questionnaire whilst learners and parents were engaged in focus group interviews (discussion groups). Information gathered through observations was also taken into account. Both the literature review and the empirical survey agreed that the learner's background that is his/her family, home environment; his/her neighbourhood and other factors of economic and social nature can impact positively or negatively on performance in the classroom. That is, according to information gathered, learners from advantaged backgrounds stand a better chance in the classroom than learners from disadvantaged backgrounds. It is evident therefore that poverty that prevails amongst the rural communities impacts on learning and performance in the examination and other classroom activities.
Thesis (M.Dev.) --University of Limpopo, 2001.
Keywords: Socio-economic status; Scholastic performance (achievement); Academic achievement -- South Africa -- Limpopo; Education, Secondary -- South Africa -- Limpopo